Barriers to the Adoption of Climate Smart Agricultural Practices among Female Farmers in Ondo State, Nigeria - Jubreel, Olasunbo Kafilat; Ogunleye, Kehinde Yewande; Ayoade, Adenike Rebecca; Ojediran, Janet Temitope; Fajobi, Deborah Tosin; Adeomi, Damilola Toluse (Pancasila International Journal of Applied Social Science, 2025)
The study examined the barriers to the adoption of climate smart agricultural practices(CSAP) among female farmers in Ondo State, Nigeria. A Multi-stage sampling procedure was used to randomly select one hundred and twenty respondents for the study. Primary data were collected from the respondents with aid of a structured questionnaire and analysed using descriptive statistics and inferential statistics. The results of this study showed the mean age of the women to be 46.68 ± 12.85. Majority (90%) of the women were married. It was also indicated from the findings of the study that the level of adoption of CSAP was generally low (34% adopters). Lack of credit facilities (x=2.93), limited decision making power (x=2.87) and lack of support and guidance by extension agents were the major barriers faced by the women farmers. Result of the Chi square analysis revealed that marital status (p=0.06) had a significant relationship with the barriers to adoption of CSAP of the women farmers. Based on the findings of the study, it was recommended that collaboration between female and male farmers especially spouses in the study area should be encouraged to facilitate adoption of CSAP by the women farmers. Government should encourage women to adopt CASP, through access to financial aids. More works in terms of extension visit, training and sensitization on CSAP should be encouraged by government and relevant agencies like the National Council on Climate Change (NCCC) and the ministry of agriculture.